Integrated multi-omics reveals distinct maternal and neonatal gut microbial and metabolic signatures associated with small for gestational age status - Bian, Xiangyu; Xu, Huisong; Li, Jianqiang; Kuang, Jian; Shi, Fangshu; Li, Xiaoqiong; Li, Jinjun (Frontiers in Microbiology, 2025)
IntroductionChildren born small for gestational age (SGA) have an elevated risk of developing metabolic disorders in later life. However, the underlying gut microbiota and metabolomic alterations in SGA mother-infant dyads remain poorly understood.MethodsWe performed an integrated analysis of fecal metagenomics, metabolomics, and short-chain fatty acids (SCFAs) profiling in 10 SGA and 10 appropriate for gestational age (AGA) mother-infant dyads at term. Taxonomic composition, microbial functional pathways, carbohydrate-active enzyme (CAZyme) profiles, differential metabolites, and metabolite pathway enrichment were systematically evaluated.Results and discussionSGA neonates exhibited reduced microbial richness (Chao1 index), distinct beta-diversity, and differential abundance of key bacterial species including increased Enterococcus faecalis and Escherichia coli. Functionally, SGA maternal subjects showed divergent profiles in CAZyme genes, with lower abundance of glycoside hydrolase family 13 subfamily 16, glycosyl transferase family 66, and carbohydrate-binding module family 6, and altered structural polysaccharide degradation capacity. Metabolomic profiling revealed significant perturbations in tryptophan metabolism pathways, notably enriched in kynurenine and taurine derivatives in SGA mother and neonates. Notably, SCFA profiles were disrupted, with increased butyrate in SGA mother and reduced propionate and isobutyrate in SGA neonates. Microbe-metabolite correlation networks revealed strong associations between SGA-specific bacterial taxa and fecal metabolites. In conclusion, our analysis identifies distinct features of the early fecal microbiome and metabolome within 48 h of birth in SGA neonates compared with AGA peers, reflecting differences in initial colonization and metabolism that warrant longitudinal follow-up.